The archaeology of knowledge traditions of the Indian Ocean World - Ray, Himanshu Prabha (Routledge, Taylor & Francis Group, 2021)
"This book examines knowledge traditions that held together the fluid and overlapping maritime worlds of the Indian Ocean in the pre-modern period, as evident in the material and archaeological record. It breaks new ground by shifting the focus from studying cross-pollination of ideas from textual sources to identifying this exchange of ideas in the archaeological and historical record. The themes covered in the book include conceptualization of the seas and maritime landscapes in Sanskrit, Arabic and Chinese narratives; materiality of knowledge production as indicated in the archaeological record of communities where writing on stone first appears; and anchoring the coasts, not only through an understanding of littoral shrines and ritual landscapes, but also by an analysis of religious imagery on coins, more so at the time of the introduction of new religions such as Islam in the Indian Ocean around the eighth century. This volume will be of great interest to researchers and scholars of archaeology, anthropology, museum and heritage studies, Indian Ocean studies, maritime studies, South and Southeast Asian studies, religious studies, and cultural studies"